2015
DOI: 10.1021/acs.est.5b03691
|View full text |Cite
|
Sign up to set email alerts
|

Human Metabolite Lamotrigine-N2-glucuronide Is the Principal Source of Lamotrigine-Derived Compounds in Wastewater Treatment Plants and Surface Water

Abstract: Wastewater and surface water samples, extracted with four solid-phase extraction cartridges of different chemistries, were suspect-screened for the anticonvulsant lamotrigine (LMG), its metabolites, and related compounds. LMG, three human metabolites, and a LMG synthetic impurity (OXO-LMG) were detected. Preliminary results showed significantly higher concentrations of OXO-LMG in wastewater effluent, suggesting its formation in the wastewater treatment plants (WWTPs). However, biodegradation experiments with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 31 publications
7
31
0
Order By: Relevance
“…3 correspond to significant skewedness of the histograms. Nevertheless, the two additional pathways found in this study are in agreement with existing literature, in which incomplete deconjugation of glucuronide metabolites to the respective parent substance was shown in wastewater for morphine 53 , lamotrigine 54 and sulfamethoxazole 55 .…”
Section: Resultssupporting
confidence: 93%
“…3 correspond to significant skewedness of the histograms. Nevertheless, the two additional pathways found in this study are in agreement with existing literature, in which incomplete deconjugation of glucuronide metabolites to the respective parent substance was shown in wastewater for morphine 53 , lamotrigine 54 and sulfamethoxazole 55 .…”
Section: Resultssupporting
confidence: 93%
“…This behaviour may be due to its hydrophilic nature (logKow <3) and chemical stability (Nakada et al, 2006). Similar behaviour is observed for lamotrigine which, in two recent studies (Bollmann et al, 2016;Zonja et al, 2016), showed a consistent concentration increase in the effluent.…”
Section: Conventional Activated Sludgesupporting
confidence: 70%
“…Metformin BDL->10000 (Margot et al, 2013;Kosma et al, 2015) Carbamazepine 54-185054- (Clara et al, 2005bNakada et al, 2006;Margot et al, 2013) Lamotrigine 13-1110 (Bollmann et al, 2016;Zonja et al, 2016) Triclosan 500-6100 (Lindstrom et al, 2002;Singer et al, 2002;Halden and Paull 2005;Ying and Kookana 2007) Industrial Chemicals…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Lamotrigine is a relatively new drug that was recently detected for the first time in wastewater, surface water and drinking water (Ferrer and Thurman, 2010). In environmental samples, lamotrigine (at concentrations of up to 1 mg L À1 ) was accompanied with its primary metabolite, lamotrigine-2-N-glucuronide (Ferrer and Thurman, 2012;Writer et al, 2013b;Zonja et al, 2015). This metabolite, though pharmacologically inactive, can undergo deconjugation in water to form the parent compound (Ferrer and Thurman, 2010).…”
Section: Introductionmentioning
confidence: 99%